Effect of vaccination with a novel GnRH-based immunocontraceptive on immune responses and fertility in rats. Issue 4 (April 2020) - Massei, G.; Cowan, D.; Eckery, D.; Mauldin, R.; Gomm, M.; Rochaix, P.; Hill, F.; Pinkham, R.; Miller, L.A.
Abstract: 1. As human-wildlife conflicts increase worldwide, novel methods are required for mitigating these conflicts. Fertility control, based on immunocontraceptives, has emerged as an alternative option to lethal methods for managing wildlife. 2. Immunocontraceptives are vaccines that generate an immune response to key components of an animal's reproductive system. Some of these vaccines target the gonadotropin-releasing hormone (GnRH) and have been used successfully as contraceptives for many wildlife species. However, the need to capture animals for treatment limits the field applications of injectable vaccines. The availability of orally delivered immunocontraceptives would increase the breadth of applications of fertility control for wildlife management. 3. This study explored a new approach to developing an oral immunocontraceptive, exploiting the bioadhesive and immunologically active properties of killed Mycobacterium avium cell wall fragments (MAF). The MAF was conjugated to a GnRH recombinant protein called IMX294, used as a GnRH-specific immunogen. 4. An initial trial using the MAF-IMX294 conjugate provided the first evidence that an orally delivered immunocontraceptive vaccine could generate anti-GnRH antibody titres in laboratory rats. 5. Increasing the dose and frequency of vaccine administered to rats, in a second trial, enhanced the immune response, eliciting titres that reduced the proportion of females giving birth. This provided the first evidence of the contraceptive effect of an oral anti-GnRH vaccine. 6. Future work is required to further increase the immunogenic effect of the oral vaccine and to establish a dosing schedule that is effective for practical field applications. Abstract : Immunology; Immune response; Vaccination; anti-GnRH vaccine; Fertility control; Human-wildlife conflicts; Immunocontraception; Oral vaccine; Wildlife management.